Heretics: Adventures with the Enemies of Science by Will Storr - Cardeña, Etzel (Journal of Scientific Exploration, 2013)
Will Storr, journalist and novelist, has written a book about people who vociferously disregard evidence that does not fit comfortably with their dogmas. Yes, many of the usual suspects are here: the holocaust denier, the creationist who ridicules evolutionary theory, and the past Thatcher science advisor who pooh-poohs global warming. But Storr shows that many debunkers and critics of nonmainstream (in our culture) beliefs are equally contemptuous of the scientific method and, in some cases such as that of the "Amazing Randi," mythologize themselves and lie in order to ridicule and frustrate their opponents. Lying is a strong word, but a refreshing virtue of Storr is that he arrives to his interviews very well-prepared and is fearless in his probes (p. 368, see also McLuhan 2010): S: (You) sometimes lie. Get carried away. R: Oh, I agree. No question of that. I don't know whether the lies are conscious lies all the time . . . S: So you've never been wrong about anything significant? R: In regard to the Skeptical movement and my work . . . No. Nothing occurs to me at the moment. In a note about his method at the end of the book (p. 392), Storr declares that his "knowledge is broad but shallow," yet he is an astute and vigorous synthesizer of many sources including the media and academic publications. The Heretics is at it most incisive when it juxtaposes replies from opposite camps, revealing just how similar they actually are despite content divergences. A telling example is from his chapter on homeopathy.